Literature Review : The Relationship of Husband's Support on Anxiety During The Labor Process - Rahayu, Mona; Mutmainnah, Muthia; Mulyani, Sri; Nurlinawati, Nurlinawati; Meinarisa, Meinarisa (Program Studi Keperawatan Universitas Jambi, 2022)
Approaching the birthing process, pregnant women experience various feelings, including anxiety. To reduce anxiety during childbirth is the presence of a maternal companion such as a husband. The husband's presence during the birthing process can have a positive effect on childbirth, namely reducing morbidity, reducing pain, shortening labor and reducing the number of births with operations such as caesarean section. Objective: To analyze research articles related to the relationship between husband's support and anxiety during the birth process. This study uses a literature study method, searching for articles using 6 electronic based articles, namely Goggle Scholar, Sematic Scholar, Pubmed, Garuda, Elsevier, Research Gate. With the keywords husband's support, anxiety, childbirth and husbands support, anxiety, childbirth process. Accredited Journal, full paper, published from 2017-2021. The results of the analysis of 11 articles showed the same result that there was a relationship between husband's support and anxiety during the birth process. This is indicated by the higher the husband's support, the lower the anxiety level of the mother giving birth. The conclusion of the article analysis results shows that there is a significant influence between the relationship between husband's support and anxiety during the birth process. So it is necessary to provide education regarding the importance of husband's support during the wife's birthing process.